OPTIMIZING THE CAPABILITY OF VILLAGE EQUIPMENT IN MANAGING VILLAGE FUNDS IN GAMPONG ALUE BEURAWE - Firdasari Firda; Nina Fahriana; Haikal Fajri (LPPM dan PM Universitas Samudra, 2021)
The management of village funds still needs to be improved so that the government always tries to encourage the development of village funds in order to achieve good management. The preparation of the RAB is an important thing that must be mastered so that the planned quality, cost, and time targets can be in accordance with the ongoing activities. The Community Service Partner is an apparatus of Alue Beurawe Village and this service aims to optimize the ability of village officials in calculating the RAB for village infrastructure. Village officials who participate in this activity will be trained and assisted to make RAB for village infrastructure. The stages of implementing activities begin with coordination with the Keuchik of Alue Beurawe Village; cooperate; make a guidebook for the preparation of the RAB along with its application; coordination of the implementation of training and mentoring activities with partners and the last stage is the implementation of training activities and assistance to village officials. Implementation of activities by conducting socialization of RAB and its constituent components, explanations of reading and understanding technical drawings, discussion of work unit price analysis ( AHSP), calculation of the volume of each work and calculation of RAB. The service output is a guidebook for preparing RAB that can be used by village officials and an application for preparing RAB with Microsoft Excel. This service can be a reference for the village in improving the capacity of human resources in the village. The benefits of this activity are expected to be able to optimize the knowledge, skills and abilities of village officials in preparing village infrastructure budgets. Keywords: budget plan, village fund,